Outdoor adventure education foundations, theory, and research - Ewert, Alan W. 1949-; Sibthorp, R. James (Champaign, IL Human Kinetics, 2014)
Outdoor Adventure Education: Foundations, Theory, and Research steeps students in the theories, concepts, and developments of outdoor adventure education, preparing them for careers in this burgeoning field. This text is based on author Alan W. Ewert's pioneering book Outdoor Adventure Pursuits: Foundations, Models, and Theories. Ewert and Sibthorp, both experienced practitioners, researchers, and educators, explore the outdoor adventure field today in relation to the changes that have occurred since Ewert's first book. The authors present a comprehensive text on outdoor and adventure foundations, theories, and research that will provide the basis for the next generation of professionals. Outdoor Adventure Education offers a comprehensive view of the expanding discipline of outdoor adventure education in its various settings. In addition to its foundational, theoretical, and conceptual insights, this text presents the following: Why This Chapter Is Important introductions that present snapshots of ideas and concepts and how they apply to future professionals; Chapter discussion and research questions to expand knowledge and research skills to support the learning gained through the book; Sidebars from well-known international researchers who present their views on the chapter topics. The book is presented in three parts. Part I explores foundational issues of outdoor adventure education, offering an overview of the field and examining both historical developments and current practices. Part II investigates theoretical constructs and extant theories, emphasizing how they inform the professional's view of program evidence, design, and implementation. In part III, the authors delve into research and evidence-based practices in the field and look at evolving trends and issues as outdoor adventure education continues to grow. Outdoor Adventure Education uses evidence, design, and implementation as its underlying themes. It shows students and professionals how to apply theories and research in constructing frameworks for outdoor adventure education experiences and how to evaluate those experiences. As such, it is an indispensable resource that prepares students and professionals alike for success in their careers in outdoor adventure education.
Part I. Foundations -- Chapter 1. Overview of Outdoor Adventure Education ; Defining Adventure ; Defining Outdoor Adventure Education ; Types of Definitions ; Evidence, Design, and Implementation ; Summary ; Issues for Further Discussion -- Chapter 2. History of Outdoor Adventure Education ; Early Explorers and Adventure Seekers ; Exploration and the Quest for Adventure ; Adventure in Transition ; The Concepts of Leisure and Recreation ; The Advent of Adventure Recreation ; Formalized Schools of Adventure Education ; Summary ; Issues for Further Discussion -- Chapter 3. Outdoor Adventure in Contemporary Practice ; Programs and Practice ; Components of the OAE Experience ; Philosophical Basis ; The Adventure Progression ; Summary ; Issues for Further Discussion -- Chapter 4. Managing Motivation, Risk, Fear, and Stress ; Motivations in OAE ; Risk and Risk Taking ; Fear in OAE ; Summary ; Issues for Further Discussion -- Part II. Theory -- Chapter 5. Theoretical Constructs Used in Outdoor Adventure Education ; Theory and Model Development ; Dissecting the Concept of Theory ; Models in Outdoor Adventure Education ; Summary ; Issues for Further Discussion -- Chapter 6. Extant Theories and Key Constructs in Outdoor Adventure Education ; Promising Explanatory Frameworks ; Key Theories ; Key Learning Constructs ; Summary ; Issues for Further Discussion -- Chapter 7. Development Across the Life Span ; Youth and Adolescents ; Emerging Adults ; Adults ; Older Adults ; Additional Views of Human Development ; Summary ; Issues for Further Discussion -- Part III. Research -- Chapter 8. Evaluation Research ; Common Purposes of Evaluation ; Case Study: The WRMC Incident Reporting Database ; Common Evaluation Techniques ; Alternative Evaluations: Best Practices and Benchmarking ; Common Limitations ; Summary ; Issues for Further Discussion -- Chapter 9. Outcomes of Participation ; Common Participation Outcomes ; Program Qualities ; Summary ; Issues for Further Discussion -- Chapter 10. State of OAE Research -- The Role of Research ; Early Research in OAE ; OAE Research Matures ; Current Trends ; Summary ; Issues for Further Discussion -- Chapter 11. Improving Research ; Challenges in OAE Research ; Strengthening Research ; Summary ; Issues for Further Discussion -- Chapter 12. Evolving Trends and Issues ; Changing Levels and Types of Use ; Impacts of Technology ; Changing Values ; Consumerism ; Future Challenges ; Summary ; Issues for Future Discussion.
Includes bibliographical references
Keywords: Adventure education; Experiential learning; Outdoor education